Establishing Technological Innovation in MSMEs For Sustainable Finance: The philosophy paradigm of Indonesia - Mujennah Mujennah; I Made Narsa; Heru Tjaraka (Ta'amul: Journal of Islamic Economics, 2025)
This study explores how financial technology (fintech) can be developed and positioned within Micro, Small, and Medium Enterprises (MSMEs) in Indonesia to support sustainable finance through a philosophical and ethical lens. The core problems addressed include unequal access to finance, the capitalist bias in technological innovation, and the lack of ethical integration in fintech development. The study aims to bridge conceptual gaps between technological innovation, ethical finance, and inclusive development. Employing a qualitative research design grounded in interpretivism and constructivism, the research integrates philosophical inquiry with literature-based analysis. Phenomenological and grounded theory approaches are used to examine ethical, behavioral, and Islamic perspectives on fintech usage among MSMEs. The findings reveal that while fintech has the potential to democratize access to finance and accelerate digital innovation, its effectiveness relies on alignment with core values such as trust, justice, transparency, and sustainability. Sharia-compliant fintech models provide an ethical alternative to conventional systems but require regulatory, infrastructural, and cultural support. The study emphasizes the need for fintech solutions that empower rather than exploit and that place human dignity and ethical responsibility at the heart of innovation. This research is among the few to examine fintech adoption among MSMEs from a philosophical perspective, combining postmodern, Islamic economic, and behavioral finance viewpoints. It offers a conceptual framework for humanizing fintech and provides ethical guidance for policymakers and innovators working toward inclusive and sustainable financial ecosystems.